Learning preferences among clinical dental students of coastal South India: A multi-centric study - Supriya Nambiar; Mahesh Jain; B Unnikrishnan; Vivek Narayan; Suresh Babu; Shaji Varghese (SRM Journal of Research in Dental Sciences, 2019)
Introduction: Dental skills based on sound theoretical knowledge are the basis for a dental student to become a good dentist. The 3rd and 4th years of Bachelor of Dental Surgery requires integration and application of clinical knowledge, skill, and attitude. However, to understand this integration, there is a paucity of literature on the dental students' learning preferences, especially in the Indian scenario. Hence, the objective of the present study is to provide information about it. Materials and Methods: VARK questionnaire (VARK is an acronym that stands for visual [V], aural [A], read [R], and kinesthetic [K] sensory modality of learning) was used to evaluate the learning preferences of clinical dental students. This multicentric study included 350 students from four dental colleges in India. Statistical Analysis: Strong preference was calculated on Microsoft Excel using the VARK guidelines. Likert scale (1–5) was used to know their perceptions of their VARK score. Results: Majority of the students were multimodal with many students showing two preferences. Kinesthetic modality was the strongest single preference and visual was the weakest single preference. Conclusion: Majority of the students are multimodal in their learning preferences with kinesthetic modality showing strong single preference. Teachers can help students to develop learning preferences based on their preferences of learning. Teaching methodology should involve all sensory modalities so that all kinds of students can actively participate in learning process.